Loneliness Versus Distress: A Comparison of Emotion Regulation Profiles. Issue 3 (14th September 2022) - Tan, Alyssa J.; Mancini, Vincent; Gross, James J.; Goldenberg, Amit; Badcock, Johanna C.; Lim, Michelle H.; Becerra, Rodrigo; Jackson, Ben; Preece, David A.
Abstract: Loneliness, a negative emotion stemming from the perception of unmet social needs, is a major public health concern. Current interventions often target social domains but produce small effects and are not as effective as established emotion regulation (ER)-based interventions for general psychological distress (i.e., depression/anxiety). Given that loneliness and distress are types of negative affect, we aimed to compare them within an ER framework by examining the amount of variance ER strategies accounted for in loneliness versus distress, and comparing the ER strategy profiles characterising them. Participants ( N = 582, M age = 22.31, 77.66% female) completed self-report measures of loneliness, distress, and use of 12 cognitive (e.g., cognitive reappraisal) or behavioural (e.g., expressive suppression) ER strategies. Regression analyses revealed that ER explained comparable variance in these constructs. Latent profile analysis identified seven profiles differing in ER patterns, with no distinct loneliness or distress profile identified. Rather, similar patterns of ER characterised these two constructs, involving the greater use of generally maladaptive strategies and the lesser use of generally adaptive strategies. However, loneliness was additionally characterised by less use of strategies involving social connection/expression. Overall, our study supports the utility of ER for understanding loneliness. Established ER-based frameworks/interventions for distress may have transdiagnostic utility in targeting loneliness.